Preoperative misdiagnosed gastrointestinal stromal tumor surgical “transferred” into gastric duplication cyst - Lazović, Ranko; Smolović, Brigita; Vučković, Ljiljana; Radunović, Miodrag (Vojnosanitetski pregled, 2018)
Introduction. Gastrointestinal duplications are rare congenital anomalies, especially in the adult population which can occur along the entire gastrointestinal tract. The rarest among them are gastric duplications, making up 2–8% of all gastrointestinal duplications. Unusual embryonic malformations can be found even in the adult population and should always be considered in the differential diagnosis of thoraco-abdominal tumors. Unclear findings during preoperative diagnostic procedures are the reason for presenting the case. Case report. We present a 33 years old female, with tumorous lesion in the stomach wall, which had the endoscopic ultrasound features of gastrointestinal stromal tumor. During surgery, it was determined that the lesion was actually a cystic formation with gelatin content and histological examination confirmed the diagnosis of gastric duplication cyst. Conclusion. Preoperative diagnosis of gastric duplication cyst has always been a challenge for clinicians, since its morphological appearance may vary. That is the reason why these anomalies are often misdiagnosed as solid tumorous lesions by imaging methods and even by the most superior ones, and set up the surgery as a part of diagnostic algorithm.